Early postoperative oral fluid intake in paediatric day case surgery influences the need for opioids and postoperative vomiting: a controlled randomized trial†This Article is accompanied by Editorial Aew450. (March 2017) - Chauvin, C; Schalber-Geyer, A.S.; Lefebvre, F; Bopp, C; Carrenard, G; Marcoux, L; Mayer, J.F.; Schwaab, C; Joshi, G.P.; Diemunsch, P
Abstract: Background: In children younger than 4 yr, it is difficult to distinguish the cause of postoperative distress, such as thirst, pain, and emergence delirium. This may lead to inappropriate treatment, such as administration of opioids. The aim of this study was to evaluate the influence of early postoperative oral fluid intake on the use of opioid analgesics and the incidence of postoperative vomiting (POV) after paediatric day case surgery. Methods: After ethics committee approval and with parental informed consent, planned day surgery patients aged 6 months to 4 yr were randomized to the liberal group (LG), in which apple juice (10 ml kg −1 ) was offered first if the Face Legs Activity Cry COnsolability (FLACC) score was ≥4 in the PACU, or to the control group (CG), in which children were treated after surgery according to the institutional opioid protocol, and drinking was allowed only upon the return to the ward. Bayesian statistical analysis was used to compare POV incidence and opioid use across groups. Results: Data from 231 patients were analysed. The incidence of POV in the LG and the CG was 11.40 and 23.93%, respectively. An opioid was needed in 14.04% (mean total dose: 0.18 mg kg −1 ) and 35.89% (mean total dose: 0.20 mg kg −1 ) of the patients in the LG and the CG. The PACU stay was 53.45 and 65.05 min in the LG and the CG, respectively (all differences were statistically significant). Conclusions: In our paediatric outpatient setting, early postoperative oral fluid intake was associated with a reduction in opioid use and POV incidence. These results deserve confirmation in other settings. Clinical trial registration: NCT02288650.